Absence of temperature effect on elution profiles on anionic and cationic ion‐exchange resins from 4°C to 28°C. (19th May 2020) - Lamboux, Aline; Hassler, Auguste; Davechand, Priyanka; Balter, Vincent
Abstract : Rationale: In labs devoted to the geochemistry of non‐traditional isotopes, chemical elution is necessary to purify the element of interest. Elution is always performed in over‐pressured and air‐conditioned clean rooms. We took advantage of an air‐conditioning failure in our lab during summer 2018 to study the effect of temperature on the characteristics of the elution profiles of ion‐exchange resins. Methods: We performed the ion‐exchange separation of copper, iron and zinc on macroporous anionic AG MP‐1 resin and that of calcium on cationic AG 50W‐X12 resin, at 28°C, prior to the measurement of their isotopic ratios by mass spectrometry. We further performed these experiments in a clean hood in a cold room at 4°C. The elution curves were processed on biological standards, i.e. bovine liver (SRM‐1577c), fetal bovine serum (FBS), bone meal (SRM‐1486) and the seawater IAPSO standard. Results: The elution profiles of major elements for each matrix, and those of copper, iron, zinc and calcium, were compared with those classically achieved at 20°C in air‐conditioned conditions. The results show that the elution profiles preserve their characteristics whatever the temperature, suggesting that partitioning coefficients between resin and solution are thermo‐independent in the range of temperature from 4°C to 28°C. Conclusions: If generalized to other matrices, notably inorganic, and to other elements, notably the extreme case of the separation of Rare Earth Elements, the present results suggest that clean labs may not have to be air‐conditioned. This would reduce installation and operating costs and have a positive effect on the environment, paving the way for the development of a "green geochemistry".